2015
DOI: 10.1002/nbm.3334
|View full text |Cite
|
Sign up to set email alerts
|

1H nuclear magnetic resonance (NMR) as a tool to measure dehydration in mice

Abstract: Dehydration is a prevalent pathology, where loss of bodily water can result in variable symptoms. Symptoms can range from simple thirst to dire scenarios involving loss of consciousness. Clinical methods exist that assess dehydration from qualitative weight changes to more quantitative osmolality measurements. These methods are imprecise, invasive, and/or easily confounded, despite being practiced clinically. We investigate a non-invasive, non-imaging (1)H NMR method of assessing dehydration that attempts to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…We hypothesize that these two participants became dehydrated over the course of the study, as supported by their baseline blood values and subsequent intake and output (table S1). This hypothesis is consistent with our previous animal dehydration experiments, which showed the same pattern of RA decrease exclusively in the muscular tissue during acute dehydration (34). Furthermore, literature shows that nonexercise-based dehydration leads to a decrease primarily in the ECF of the muscle (35,36).…”
Section: Mri: Relative Amplitudessupporting
confidence: 93%
“…We hypothesize that these two participants became dehydrated over the course of the study, as supported by their baseline blood values and subsequent intake and output (table S1). This hypothesis is consistent with our previous animal dehydration experiments, which showed the same pattern of RA decrease exclusively in the muscular tissue during acute dehydration (34). Furthermore, literature shows that nonexercise-based dehydration leads to a decrease primarily in the ECF of the muscle (35,36).…”
Section: Mri: Relative Amplitudessupporting
confidence: 93%
“…Some of these devices, such as the NMR‐MOUSE, are commercially available. Some studies have explored the use of such ultraportable “single‐sided” spectrometers and relaxometers for medical applications, such as for skin profiling, mammographic, and hydration monitoring applications. These single‐sided systems are far smaller than traditional MR scanners where the patient is interior to the magnet and thus have the potential to be true “point‐of‐care” devices.…”
Section: Introductionmentioning
confidence: 99%
“…A T2‐based MR measurement can provide information related to the composition and volume of a fluid compartment. Our group previously demonstrated that multicomponent T2 relaxometry via whole‐body NMR can identify fluid depletion as a decrease in the signal amplitude from the lean tissue component . This led us to explore the localization of a similar measurement toward the skeletal muscle tissue with the ultimate goal of miniaturizing the magnetic resonance (MR) sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Our group previously demonstrated that multicomponent T2 relaxometry via whole-body NMR can identify fluid depletion as a decrease in the signal amplitude from the lean tissue component. 36 This led us to explore the localization of a similar measurement toward the skeletal muscle tissue with the ultimate goal of miniaturizing the magnetic resonance (MR) sensor. Multicomponent T2 relaxometry via MRI has demonstrated sensitivity toward distinct fluid compartments within skeletal muscle tissue.…”
mentioning
confidence: 99%